Would EFL Students learn better through the Implementation of NHT Model?: A CAR Study for Reading Comprehension Improvement of Junior Level - Oktin Kristina Hutapea; Seli Marlina Radja Leba; Tego Tego (Journal of English Culture, Language, Literature and Education, 2023)
This class action research aims to apply the Numbered Head Together learning model to improve student learning outcomes in English subjects, especially for reading comprehension skills at the junior level, namely in class VII SMP Negeri 1 Merauke in the 2022/2023 academic year. This research is a Classroom Action Research (CAR), where Classroom Action Research (CAR) is research conducted in two stages of the cycle, where each cycle I and cycle II is carried out twice the learning process meeting. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The subjects in this study were 32 seventh grade students. The success indicator of this study is if 75% of students can achieve the Minimum Completeness Criteria (KKM) value of 70. The results showed that the application of the Numbered Head Together (NHT) Learning Model in class VII SMP Negeri 1 Merauke showed an increase in the completeness of students' learning achievement in cycle I with an average of 61.65% increasing to 80.28% in cycle II. The percentage of learning completeness also increased from cycle I by 12.5% increasing to 100% in cycle II. In addition, There was also a very significant increase in each teacher and student activity based on the observation sheet. Where in cycle I the teacher's activities were at 89.28% and students at 66.07%, then increased in cycle II, where teacher activities became 96.42% and students at 91.07%.